2020
DOI: 10.1007/s40744-020-00254-z
|View full text |Cite
|
Sign up to set email alerts
|

Ixekizumab Improves Patient-Reported Outcomes in Non-Radiographic Axial Spondyloarthritis: Results from the Coast-X Trial

Abstract: Introduction Ixekizumab, an interleukin-17A antibody, has shown efficacy in non-radiographic axial spondyloarthritis (nr-axSpA). The objectives of this analysis were (a) to measure improvement in ixekizumab-treated patients in Assessment of Spondyloarthritis International Society (ASAS) response domains and other patient-reported outcomes (PROs) and (b) to determine how ASAS responses were associated with changes in patient global disease activity (PtGA), spinal pain, function, stiffness, fatigue,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 22 publications
(37 reference statements)
1
3
0
1
Order By: Relevance
“…Furthermore, positive improvements in pain, as well as physical function and general HRQoL as measured by SF-36 PCS and ASAS HI, were consistent with previous studies with IL-17 inhibitors [ 28 , 29 ]. Results were also consistent with studies with TNFi treatments in nr-axSpA [ 30 32 ].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Furthermore, positive improvements in pain, as well as physical function and general HRQoL as measured by SF-36 PCS and ASAS HI, were consistent with previous studies with IL-17 inhibitors [ 28 , 29 ]. Results were also consistent with studies with TNFi treatments in nr-axSpA [ 30 32 ].…”
Section: Discussionsupporting
confidence: 90%
“…Several studies have demonstrated that improvements in PROs are associated with improved clinical measures of disease activity and symptoms, which is critical in axSpA given the high disease burden [ 28 , 30 , 33 35 ]. A significantly greater proportion of patients with active nr-axSpA treated with upadacitinib vs. placebo achieved the primary endpoint of ASAS40 at week 14 as well as the threshold of ASDAS inactive disease [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…The results after 52 weeks showed that the initial improvements noted above were maintained. Post hoc analysis of the COAST-X, COAST-W, and COAST-V trials shows that patient-reported outcomes relating to quality of life, fatigue, function, health status, and work productivity improved with ixekizumab [100][101][102][103]. Interestingly, these improvements in patient-reported outcomes were correlated with the patients' ASAS20/40 response [100,102].…”
Section: Targeting Il-17 In Ankylosing Spondylitis and Psoriatic Arth...mentioning
confidence: 97%
“…Post hoc analysis of the COAST-X, COAST-W, and COAST-V trials shows that patient-reported outcomes relating to quality of life, fatigue, function, health status, and work productivity improved with ixekizumab [100][101][102][103]. Interestingly, these improvements in patient-reported outcomes were correlated with the patients' ASAS20/40 response [100,102]. Further analysis of the clinical trial data showed that 75% of patient had no radiographic progression over 2 years [104].…”
Section: Targeting Il-17 In Ankylosing Spondylitis and Psoriatic Arth...mentioning
confidence: 99%
“…Además de la inhibición de la IL-23, se han evaluado diferentes tratamientos dirigidos a moléculas efectoras de la inmunidad tipo 3 como la IL-17 y la IL-22. La inhibición de la IL-17 ha sido revisada ampliamente y los ensayos clínicos, tanto de secukinumab como de ixekizumab (los dos agentes que bloquean la IL-17) han demostrado efectividad y han resultado muy valiosos en el entendimiento de las enfermedades inmunomediadas relacionadas con PsO [116][117][118][119][120] y SpA 117,[121][122][123][124] . De forma interesante, se ha reportado que la inhibición de IL-17 en pacientes con EII resulta en un agravamiento del daño intestinal, probablemente relacionado con una disminución de la función de barrera 125,126 .…”
Section: Inhibición De La Il-23unclassified